CONDITIONAL RELATIONSHIPS IN CURRENT UZBEK AND ENGLISH (Uzbek Scholar Journal, 2025)
This article examines the representation of conditional relations in contemporary Uzbek and English. By comparing the structural, semantic, and pragmatic aspects of conditional constructions, the study highlights linguistic and cultural differences and similarities in both languages. It also addresses translation problems that arise when transferring conditional meanings across languages, particularly in literary contexts. Functional grammar, contrastive linguistics, and corpus-based analysis are used to support the study. The findings suggest that conditionals in Uzbek provide greater syntactic flexibility, while English has stricter structural constraints. The study suggests strategies for effective translation and pedagogical use of conditional forms.